The motivation of female social entrepreneurs in Lundu district, Sarawak, Malaysia - Yee, Lai Ling; Johari, Shazali; Emang, Diana; Thoo, Poh Yee (Research Institute of Asian Women, 2022)
Social entrepreneurship is a type of entrepreneurship that pursues opportunities to solve social, economic, and environmental issues. As a pioneering study exploring McClelland's theory of needs in the context of social entrepreneurship, this study investigated the factors that influence the motivation of female social entrepreneurs in Lundu District of Sarawak, Malaysia. This study was carried out with 150 respondents using a census method, and the results showed that female social entrepreneurs were most motivated to engage as social entrepreneurs by the need for affiliation, followed by the need for achievement and the need for power. The multiple linear regression results indicated that attendance at courses and training was the most influential factor that positively influenced all three motivational dimensions. Accordingly, policymakers should incorporate human resource managers and other training providers to tailor suitable courses and training for communities. In contrast, ethnic community leaders should strengthen community bonding through various programs to enhance all three needs among the local communities, especially the need for affiliation, to encourage them to engage in social entrepreneurship. Theoretically, this study makes McClelland’s theory of needs more robust by applying it to the social entrepreneurship phenomenon and expands the literature on social entrepreneurship in the context of developing countries.